Effect of crude saponins from Gaultheria trichophylla extract on growth inhibition in human colorectal cancer cells (Bangladesh Journal of Pharmacology, 2015)
The genus Gaultheria also comprised of species with reported cytotoxic activities. Current research work  was carried out to evaluate G. trichophylla crude extract and respective saponins fraction against human colorectal cancer cell line (Caco-2) based on cell viability assays. Caco-2 cells treated with the crude extract showed significant growth  inhibition (p< 0.001) in a dose dependent manner with apparent IC50 value of 200 ?g/mL and 100 ?g/mL in MTT and NRU assays respectively. The fractioned crude saponins showed an enhanced response and inhibited the growth of Caco-2 by 93.6 and 97.4% in MTT and NRU assays respectively, with compared to actinomycin-D (65%). The DAPI staining of cell treated with crude saponins observed under confocal microscope showed shrunken nuclei with apparent nuclear fragmentation and chromatin condensation indicating apoptosis mode of cell death. The study exhibited that the G. Trichophylla saponins induced apoptosis of Caco-2 cell lines. This study provides new evidences to further explore this plant for the novel targets in anticancer drug development.